Proposed best practices of financial information disclosure for Zakat institutions: a case study of Malaysia - Htay, Sheila Nu Nu; Salman, Syed Ahmed (IDOSI Publication, 2014)
Zakat is a compulsory levy imposed on the Muslims who are relatively financially well. Zakat plays a crucial role in Islamic economy since it is one of the important economic tools to elevate the poverty. The confidence of the zakat payers on the process of zakat collection and distribution performed by the zakat institutions plays the essential role in order to collect more zakat. Public confidence can be gained by transparent and full disclosure of financial information of the institutions. Many international organizations such as AAOIFI and IFSB and local standard setting bodies like MASB have provided the accounting guidelines and standards for the transparency of the companies. The prevailing standards focus on the profit oriented institutions and to the extent of our knowledge, no guideline has been issued for the financial reporting aspect of zakat institutions. Thus, the objective of this research is to propose best practices of financial information disclosure for zakat institutions. Both primary and secondary data are used in this study. Primary data is collected from the questionnaire and secondary data is obtained from the relevant books, articles and internet resources. In addition, library research and in terms of data analysis, descriptive statistics is employed. The results from the questionnaire reveal that there is a need for the guidelines for financial information disclosure. The respondents highlight that disclosure on accounting policy and changes and board of trustees, risk management, statement of internal control, important highlights, disclosure on zakat collection and distribution and statement of cash flow are the essential components of reporting. The findings will be the interest of zakat authorities, regulators, zakat payers, zakat recipients and researchers.